Impact of Covid19 lockdown on NSE India indexes - Basumatary, Priyo; Sharma, Dr. Siddharth Nayan; Hazarika, Dr. Balin (The journal of contemporary issues in business and government, 2021)
The covid19 pandemic had forced the Government of India to impose a nationwide lockdown. The present study aims to investigate the impact of lockdown on various NSE India indexes. Event study technique which is used to calculate the abnormal return of a stock has been used. The closing price of 11 NSE India indexes has been used for the analysis. A window period of (+40, -40) days pre and post the event day has been selected. Two-tailed test has been used to test the null hypothesis both at 5% and 1% level of significance. The result of the study shows that most of the indexes had abnormal returns.